2005
DOI: 10.1007/s00264-005-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gluteal fasciocutaneous rotational flaps and myocutaneous flaps for the treatment of sacral sores

Abstract: To compare the outcomes of gluteal fasciocutaneous rotational flaps and myocutaneous flaps in the treatment of sacral sores, together with a review of surgical complications in two matched cohorts. Thirty-eight patients (18 gluteal fasciocutaneous rotational flaps and 20 myocutaneous flaps) were reviewed retrospectively at a mean follow-up of 58 weeks. The rate of healing of the sore, the sore healing time, and the incidence of surgical complications, together with rate of recurrence, were obtained by chart re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
0
20
0
5
Order By: Relevance
“…6,8,26 The wide disparity in reported recurrence rates is due, in large part, to a lack of standard definitions for endpoints, as well as wide variation in length of follow-up, with shorter studies reporting much lower recurrence rates. 27,28 Pressure ulcer recurrence has been established to plateau at 15 to 22 months postoperatively (well outside the 30-day window tracked in NSQIP). 6,26,29,30 However, failure of surgical treatment appears to occur on a continuum from immediate operative failure through dehiscence to recurrence, with earlier failures being associated with the patient's healing capacity and tissue quality, and later recurrences associated with failure of preventative measures.…”
Section: Discussionmentioning
confidence: 98%
“…6,8,26 The wide disparity in reported recurrence rates is due, in large part, to a lack of standard definitions for endpoints, as well as wide variation in length of follow-up, with shorter studies reporting much lower recurrence rates. 27,28 Pressure ulcer recurrence has been established to plateau at 15 to 22 months postoperatively (well outside the 30-day window tracked in NSQIP). 6,26,29,30 However, failure of surgical treatment appears to occur on a continuum from immediate operative failure through dehiscence to recurrence, with earlier failures being associated with the patient's healing capacity and tissue quality, and later recurrences associated with failure of preventative measures.…”
Section: Discussionmentioning
confidence: 98%
“…16,18 The wide disparity in reported recurrence rates is due, in large part, to a lack of standard definitions for endpoints, as well as wide variation in length of follow-up, with shorter studies reporting much lower recurrence rates. 27,28 Despite advances in surgical technique and postoperative management, studies of flap coverage have shown no improvements. 16,29 -31 Within the last 10 years, reported dehiscence rates have ranged between 9 and 45 percent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wong et al described the difference in complications between 18 gluteal fasciocutaneus rotational and 20 myocutaneus flaps. 22 The 12-month follow-up investigation revealed that complications in the first group was 17% and in the second group 15%. 22 Findings were not presented in a useful manner, because the grouping of flaps was too general.…”
Section: Discussionmentioning
confidence: 99%
“…22 The 12-month follow-up investigation revealed that complications in the first group was 17% and in the second group 15%. 22 Findings were not presented in a useful manner, because the grouping of flaps was too general. It does not account for all factors affecting the appearance of complications as discussed above.…”
Section: Discussionmentioning
confidence: 99%